Alumina sol, preparation method and application thereof, and preparation method of catalytic cracking catalyst
By reacting polymer aluminum chloride solution with aluminum to prepare aluminum sol, the problems of high production cost and complex preparation process are solved, and efficient preparation and performance improvement of catalytic cracking catalysts are achieved.
Patent Information
- Application Number
- CN202311409636.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
The existing aluminum sols have high production costs and complex preparation process, which is difficult to meet the efficient preparation needs of catalytic cracking catalysts.
Partial polymer aluminum chloride solution is used to replace aluminum and hydrochloric acid, and aluminum is prepared by reacting with aluminum to simplify the preparation process and reduce costs.
The production cost of aluminum sol is significantly reduced, the bonding performance of aluminum sol is improved, and the wear strength of the catalytic cracking catalyst is enhanced.
Smart Images

Figure BDA0004517703000000121 
Figure BDA0004517703000000131 
Figure BDA0004517703000000141
Abstract
Description
Technical Field
[0001] The invention relates to the field of aluminum sol, and in particular to aluminum sol and a preparation method and application thereof, as well as a preparation method of a catalytic cracking catalyst. Background Art
[0002] Fluidized catalytic cracking is the most important means of secondary processing of crude oil. With the increasing heaviness and inferiority of FCC feed, the content of molecular sieves in the catalyst has increased from 15-20% in the early days to 35% or even more than 40% at present. With the increase of molecular sieve content, the wear index and sphericity of the catalyst have become a very important issue in the catalyst preparation process. The catalyst must meet certain strength requirements and form microsphere particles with a particle size of 20-150 microns and an average particle size of about 60-80 microns to meet the normal flow operation of the catalytic cracking catalyst in the reaction device.
[0003] At present, the FCC catalyst products in my country are mainly semi-synthetic molecular sieve catalysts, which have many preparation methods. The main method is to mix kaolin with colloid first, and then spray-dry the slurry obtained by mixing the colloid slurry mixed with kaolin and Y-type molecular sieve to make a microsphere catalyst; calcine the spray-dried catalyst, and then wash it with water to remove the Na formed during the reaction. + After drying, a semi-synthetic molecular sieve catalyst is made. As the content of molecular sieve, the active component of the catalyst, increases, a semi-synthetic process using kaolin as the matrix, molecular sieve as the active component, and various silicon / aluminum gels as binders is used. The preparation process is simple, the preparation cost is low, and it has good strength at a high molecular sieve content.
[0004] How to continue to improve the catalyst gelling process in the semi-synthetic catalyst process has become a very important issue in the preparation process: 1) Improve productivity, reduce energy consumption, reduce the use of molecular sieves, and reduce costs. 2) Form a good sphericity. The purpose of spray drying is to evaporate excess water in the slurry at a certain temperature. When the solid content is low, more water needs to be evaporated, and the residence time of the material in the drying tower is the same, so more evaporation heat is required or the drying temperature is high. In this way, the water escapes rapidly from the inner surface of the particles at high temperature to form hollow spheres or microspheres with apple stalks. On the one hand, the catalyst strength is deteriorated, and on the other hand, it is easy to break during fluidization in the FCC re-regeneration system. 3) Improve the preparation method of the binder, improve the bonding performance of the binder, and make the binder particles more uniform through the improvement of the binder, so that it plays a better role in series bonding in the catalyst gelling process, while reducing the blockage of the molecular sieve channels and improving the activity of the catalyst. 4) Develop a more suitable matrix. The matrix is the cracking medium of macromolecules in the catalytic cracking process. The pore structure of the matrix needs to be large enough to meet the current cracking process of macromolecules in heavy oil, increase the catalyst's ability to crack heavy oil and the thermal stability of the catalyst activity. 5) Reduce the viscosity of the catalyst, reduce the resistance of the catalyst colloid transport, improve the quality of the catalyst spray, and reduce the blockage of the catalyst spray tower.
[0005] Aluminum sol is a high temperature resistant and good bonding agent widely used in the bonding of hydrocarbon cracking catalysts. There are many methods for preparing aluminum sol, and the raw materials are also various. Among them, there is a preparation method using aluminum and hydrochloric acid to synthesize aluminum chloride. CN200510064782.6 discloses a high Al 13 Polyaluminium chloride crystal and preparation method thereof, the method comprises reacting metallic aluminium with hydrochloric acid or aluminium chloride solution, or reacting aluminium hydroxide or aluminium oxide with aluminium chloride solution, or electrolysing, electrodialysing, exchanging anion resins and distilling water to aluminium chloride solution; the concentration of the above HCl is 0.1-3 mol / kg, the concentration of AlCl3 solution is 0.1-2.3 mol / kg, the reaction temperature is 20-200°C, the reaction time is 1-72 hours, the hydroxyaluminium ratio of the hydrolysis solution is controlled to be 0.1-2.8, then filtering and removing residues at 20-100°C, freezing or evaporating crystallization at 0-100°C, solid-liquid separation at 0-100°C, and drying the product at 40-90°C to prepare high Al 13 Polyaluminium chloride crystals, with a basicity of more than 61%, a total aluminium (Al2O3) of more than 33%, water insoluble matter of less than 0.3%, and the key flocculation component Al 13 (Al b ) reaches more than 90%, which meets the requirements of national standard GB15892-2004 for superior products. Flocculation test shows that: high Al 13 The flocculation effect of polyaluminium chloride crystals is significantly better than that of commercially available solid polyaluminium chloride, aluminium chloride and aluminium sulfate.
[0006] CN202010333301.1 discloses a method for preparing aluminum gel and polyaluminium chloride, and belongs to the technical field of aluminum gel and polyaluminium chloride preparation. It mainly provides a method for preparing highly active aluminum gel and polyaluminium chloride with high purity, low energy consumption and no waste residue. Highly active aluminum gel is prepared by neutralizing the pH to 4-8 with aluminum salt solution or dilute acid and sodium aluminate, potassium aluminate or dilute alkali solution within a certain period of time, and then the aluminum gel and the one-step liquid for preparing polyaluminium chloride are kept warm at 65-95°C for 0.5-2h to obtain polyaluminium chloride with a basicity of less than 90%. The aluminum gel prepared by the invention is a high-purity amorphous hydrated alumina, and when further preparing polyaluminium chloride, the solution is clear and transparent, does not require filter pressing or sedimentation, does not produce waste residue, does not require cooling during the preparation process, has a short production time, low energy consumption, and a high purity of the finished polyaluminium chloride.
[0007] Although the existing technology has optimized the preparation process of aluminum sol to a certain extent, it still has the defects of high cost and complicated preparation process. Summary of the invention
[0008] The purpose of the present invention is to overcome the problems of high production cost and complicated preparation process of aluminum sol in the prior art, and to provide an aluminum sol and its preparation method and application as well as a preparation method of a catalytic cracking catalyst. The present invention adopts a part of polyaluminum chloride solution to replace aluminum and hydrochloric acid, so as to achieve the effect of reducing cost and increasing efficiency, and further improve the bonding performance of aluminum sol.
[0009] In order to achieve the above object, the first aspect of the present invention provides a method for preparing aluminum sol, which comprises reacting a polyaluminum chloride solution with aluminum to obtain an aluminum sol; wherein the method for preparing the polyaluminum chloride solution comprises the following steps:
[0010] (1) Under the condition of introducing water vapor, aluminum hydroxide and hydrochloric acid are reacted at a temperature above 100° C. and a reaction time of more than 3 hours;
[0011] (2) The product obtained by the reaction in step (1) is allowed to stand, and the supernatant is used as a polyaluminium chloride solution.
[0012] Preferably, calculated on the basis of aluminum element, the mass ratio of the polyaluminum chloride solution to aluminum is 2.5-3.5:8.5-9.5.
[0013] The second aspect of the present invention provides aluminum sol prepared by the method described in the first aspect.
[0014] The third aspect of the present invention provides the use of the aluminum sol described in the second aspect in the preparation of a catalytic cracking catalyst.
[0015] The fourth aspect of the present invention provides a method for preparing a catalytic cracking catalyst, wherein the method comprises: slurrying a binder, clay and a molecular sieve to obtain a catalyst slurry, and spray-drying the catalyst slurry, wherein the binder contains the aluminum sol described in the second aspect of the present invention.
[0016] The preparation method provided by the present invention has a simple process and is easy to industrialize; the method provided by the present invention can use polyaluminium chloride solution to replace part of the metal aluminium, which significantly reduces the production cost of the aluminium sol. In addition, under the same other conditions, the wear strength of the catalytic cracking catalyst prepared by using the aluminium sol provided by the present invention is significantly improved. DETAILED DESCRIPTION
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0018] The first aspect of the present invention provides a method for preparing aluminum sol, which comprises reacting a polyaluminum chloride solution with aluminum to obtain an aluminum sol; wherein the method for preparing the polyaluminum chloride solution comprises the following steps:
[0019] (1) Under the condition of introducing water vapor, aluminum hydroxide and hydrochloric acid are reacted at a temperature above 100° C. and a reaction time of more than 3 hours;
[0020] (2) The product obtained by the reaction in step (1) is allowed to stand, and the supernatant is used as a polyaluminium chloride solution.
[0021] In step (1) of the present invention, aluminum hydroxide and hydrochloric acid are reacted as long as the reaction temperature is above 100°C and the reaction time is above 3h. Preferably, in step (1), the reaction temperature is 100-140°C, for example, 100°C, 110°C, 120°C, 130°C or 140°C, the reaction time is 3-5h, and the pressure is 0.1-0.6MPa, more preferably 0.2-0.5MPa. This preferred embodiment is more conducive to improving the dissolution rate of aluminum hydroxide and reducing reaction time and energy consumption.
[0022] According to the present invention, preferably, the mass fraction of the hydrochloric acid is 31-36%, for example, 31%, 32%, 33%, 34%, 35% or 36%.
[0023] The present invention has a wide selection range for the source of the hydrochloric acid, and preferably the hydrochloric acid is industrial hydrochloric acid.
[0024] In step (1), there is no particular limitation on the specific operation of the reaction, which can be carried out in a reactor. Preferably, aluminum hydroxide and optionally water are added to a reactor, hydrochloric acid is added, water vapor is introduced, and the temperature is continuously raised to above 100° C. to react.
[0025] According to the present invention, specifically, the reactor can be a conventional reactor that is resistant to acid, high temperature and pressure. For example, the reactor can be made of enamel or zirconium.
[0026] According to a preferred embodiment of the present invention, the reaction is carried out under stirring conditions. There is no particular limitation on the stirring rate and method, and the reaction can be carried out according to conventional means in the art.
[0027] In the present invention, water vapor is introduced during the reaction process to achieve the purpose of rapid temperature rise and reaction speed increase. There is no particular limitation on the specific method of introducing water vapor, for example, water vapor can be added through an internal coil or directly introduced into the reaction solution for reaction.
[0028] In the present invention, the aluminum hydroxide, distilled water and industrial hydrochloric acid in step (1) are all conventional chemicals well known to those skilled in the art, wherein the aluminum hydroxide may be of industrial grade.
[0029] According to the present invention, preferably, in step (1), the amount of aluminum hydroxide and hydrochloric acid added is such that the mass percentage of aluminum in the obtained polyaluminum chloride solution is 5-9%, the mass percentage of chlorine is 20-27%, and the mass ratio of aluminum to chlorine is 0.2-0.45; further preferably, in step (1), the amount of aluminum hydroxide and hydrochloric acid added is such that the mass percentage of aluminum in the obtained polyaluminum chloride solution is 5-8%, the mass percentage of chlorine is 20-25%, and the mass ratio of aluminum to chlorine is 0.25-0.35. Those skilled in the art can select the amount of aluminum hydroxide and hydrochloric acid added according to the aluminum and chlorine contents required in the above polyaluminum chloride.
[0030] According to the present invention, preferably, the method further comprises cooling the product obtained by the reaction in step (1) before the standing in step (2), preferably cooling it to below 60° C., more preferably cooling it to 30-50° C. This method is more conducive to reducing the corrosion of the high temperature of the reaction liquid to the transfer pipeline.
[0031] According to the present invention, there is no particular limitation on the device for the standing in step (2), and it can preferably be carried out in a storage tank. Preferably, the standing time in step (2) is more than 3 hours, preferably 3-12 hours.
[0032] According to the present invention, the product obtained by the reaction in step (1) can be transferred to the storage tank by a transfer pump. In this embodiment, the standing time is more than 8 hours, preferably 8-12 hours. The use of this preferred embodiment is more conducive to ensuring that the added excess aluminum hydroxide settles to the bottom of the tank and returns to the reactor through the regular slag cutting port at the bottom of the tank. The slag cutting port is lower than the discharge port, and is generally lower than 3-5m in industry. Preferably, the storage tank is made of acid-resistant material.
[0033] According to a preferred embodiment of the present invention, the product obtained by the reaction in step (1) can also be transferred into a storage tank using an acid-resistant filter. In this preferred embodiment, the standing time can be reduced to less than 4 hours, preferably 3-4 hours. The material filtered out of the acid-resistant filter is preferably added back into the reactor to achieve the reuse of aluminum hydroxide.
[0034] According to the present invention, preferably, the pH value of the polyaluminium chloride solution obtained in step (2) is less than 1, more preferably 0.1-0.5.
[0035] According to the present invention, preferably, the specific gravity of the polyaluminium chloride solution obtained in step (2) is 1.1-1.4 g / mL, preferably 1.24-1.4 g / mL. In the present invention, the specific gravity refers to the mass of all solid materials per unit volume.
[0036] In the present invention, the supernatant obtained by standing in step (2) is used as the polyaluminium chloride solution, and the lower layer material is preferably recycled to step (1) to provide at least part of the aluminium hydroxide. Specifically, the lower layer material can be recycled to the reactor through the cutting port.
[0037] According to the present invention, preferably, the mass ratio of the polyaluminium chloride solution to aluminium is 2.5-3.5:8.5-9.5, preferably 2.5-3:8.5-9. This preferred embodiment is more conducive to improving the reaction speed and ensuring the product quality.
[0038] According to the present invention, preferably, the conditions for reacting the polyaluminium chloride solution with aluminium (for example, elemental aluminium) include: a reaction temperature of 75-100°C, for example, 75-99°C, and a reaction time of 12-25h; further preferably, the reaction temperature is 85-95°C, and the reaction time is 12-20h.
[0039] According to a preferred embodiment of the present invention, the method comprises: adding polyaluminium chloride solution and elemental aluminium into a reactor together, heating to 65-80°C, and then reacting for 12-25 hours at a reaction temperature of 85-100°C.
[0040] The second aspect of the present invention provides an aluminum sol prepared by the method described in the first aspect. Preferably, the aluminum sol has an aluminum content of 11-12.5% by weight, a chlorine content of 7-11% by weight, a pH value greater than 2.6, and a specific gravity of 1.2-1.4; further preferably, the aluminum sol has an aluminum content of 11-12% by weight, a chlorine content of 8-11% by weight, a pH value greater than 2.7, such as 2.7-3.2, and a specific gravity of 1.3-1.4.
[0041] The third aspect of the present invention provides the use of the aluminum sol described in the second aspect in the preparation of a catalytic cracking catalyst.
[0042] The fourth aspect of the present invention provides a method for preparing a catalytic cracking catalyst, wherein the method comprises: slurrying a binder, clay and a molecular sieve to obtain a catalyst slurry, and spray-drying the catalyst slurry, wherein the binder contains the aluminum sol described in the second aspect of the present invention.
[0043] According to a preferred embodiment of the present invention, the binder is a dual aluminum binder of pseudo-boehmite and the aluminum sol provided by the present invention.
[0044] The clay described in the present invention is a clay raw material well known to those skilled in the art, and commonly used clay types can be used in the present invention. For the present invention, the clay is preferably one or more of kaolin, halloysite, montmorillonite, diatomite, halloysite, pseudo-haloysite, saponite, rectorite, sepiolite, attapulgite, hydrotalcite and bentonite. Among them, sepiolite is a magnesium-rich fibrous silicate clay mineral, in which silicon-oxygen tetrahedrons and magnesium-oxygen octahedrons alternate with each other, and have layered and chain-like transitional structural characteristics. Using acid-modified sepiolite as an FCC catalyst matrix can effectively improve the specific surface area, pore volume and mesopore volume of the catalyst, and can strengthen the anti-heavy metal effect of the catalyst. While kaolin and pseudo-haloysite have relatively close properties, halloysite has a large specific surface area, a large pore volume, and a pore size distribution showing that there are fewer macropores and more mesopores. Halloysite also has the characteristics of large surface acidity, high micro-activity index, and good pore structure stability. According to the present invention, the clay is preferably one or more of sepiolite, kaolin and halloysite.
[0045] In the present invention, the molecular sieve is a molecular sieve raw material well known in the art. All types of molecular sieves commonly used in the art can be used in the present invention. The molecular sieves preferably referred to in the present invention are REY, REHY, REUSY, USY, Y zeolite modified with different silicon-aluminum ratios prepared by gas phase chemical method (SiCl4 de-Al and Si supplementation method), liquid phase chemical method ((NH4)2SiF6 aluminum extraction and silicon supplementation method) and other methods, or mixtures thereof, as well as ZSM-5 type and β type zeolites or mixtures thereof containing other types of high silicon-aluminum ratios.
[0046] According to a preferred embodiment of the present invention, the method for preparing the catalytic cracking catalyst comprises:
[0047] (1) slurrying clay and water, then adding pseudo-boehmite (preferably acidified pseudo-boehmite), and stirring to obtain slurry A;
[0048] (2) slurrying the molecular sieve with water to obtain a molecular sieve slurry;
[0049] (3) Slurry A and molecular sieve slurry are sequentially added to the aluminum sol, and slurry is performed to obtain catalyst slurry, and the catalyst slurry is spray-dried.
[0050] According to the present invention, preferably, the acidified pseudo-boehmite is obtained by the following method: mixing the pseudo-boehmite with water, and then adding hydrochloric acid thereto under stirring conditions for acidification until the peptized state is obtained. The specific acidification process can be appropriately adjusted by those skilled in the art according to the specific circumstances, and the present invention has no particular limitation thereto.
[0051] According to the method for preparing the catalytic cracking catalyst of the present invention, the solid content of the catalyst slurry is preferably above 35 wt %, preferably 35-45 wt %.
[0052] According to a preferred embodiment of the present invention, in the catalyst slurry, based on the dry weight of the catalyst slurry (800°C, 1 hour ignition loss content), the content of molecular sieve is 10-50% by weight, preferably 25-35% by weight; the content of clay is 10-50% by weight, preferably 35-45% by weight; the content of aluminum sol (calculated as Al2O3) is 10-30% by weight, preferably 15-25% by weight; the content of pseudo-boehmite is 2-25% by weight, preferably 6-20% by weight.
[0053] According to the preparation method of the present invention, preferably, the catalytic cracking catalyst is obtained by calcining after spray drying. More preferably, the method further comprises: washing and drying the calcined catalyst. The conditions of spray drying, calcining, washing and drying can all be conventional operations in the art, and the present invention will not repeat them here.
[0054] The aluminum sol of the present invention uses a polyaluminum chloride solution to replace part of the metal aluminum while maintaining its own bonding performance, which significantly reduces the production cost of the aluminum sol and further reduces the manufacturing cost of the catalytic cracking catalyst.
[0055] It should be noted that, unless otherwise specified, in the present invention, the percentage content and percentage are all by mass percentage content and mass percentage.
[0056] The present invention will be described in detail below by way of examples. In the following examples,
[0057] The raw material specifications used in the catalyst preparation example are as follows:
[0058] Aluminum hydroxide: industrial grade, alumina content 65%, produced by Shandong Aluminum Plant;
[0059] Hydrochloric acid: mass concentration 36%;
[0060] Aluminum granules: industrial grade, produced by Catalyst Qilu Branch;
[0061] Kaolin: solid content 81.2% by weight, produced by China Kaolin Co., Ltd. (Suzhou);
[0062] Y-type molecular sieve: produced by Qilu Branch of Sinopec Catalyst Co., Ltd., solid content 80% by weight;
[0063] Alumina sol A: industrial grade, solid content 21.7%, produced by aluminum particles and hydrochloric acid, produced by Sinopec Catalyst Co., Ltd. Qilu Branch;
[0064] Pseudo-boehmite: industrial grade, solid content 62%, produced by Shandong Aluminum Plant.
[0065] Example 1
[0066] According to the formulation in Table 1 below, add 1 kg of materials into a reactor, add distilled water first, then add aluminum hydroxide powder, turn on stirring, add industrial hydrochloric acid, steam heat to control the temperature of the reactor at 100-102°C, reaction pressure 0.2 MPa, react for 4 hours, then cool to 50°C, let stand for 8 hours, take the supernatant AL-1 for use, analyze its composition, see Table 2.
[0067] The obtained supernatant AL-1 (polyaluminium chloride solution) and aluminium particles were added to a three-necked flask, wherein the mass ratio of the polyaluminium chloride solution to the aluminium particles was 3:9. A condensation reflux device was set on the top of the three-necked flask to reflux the water vapor carried away by the hydrogen in the reaction. The reaction liquid was heated to 75°C by electricity, and then reacted for 16 hours to obtain aluminium sol 1. The analytical data of the aluminium sol are listed in Table 3.
[0068] Example 2
[0069] According to the formulation in Table 1 below, add 1 kg of materials into a reactor, add distilled water first, then add aluminum hydroxide powder, turn on stirring, add industrial hydrochloric acid, steam heat to control the temperature of the reactor at 106-110°C, reaction pressure 0.4 MPa, react for 4 hours, then cool to 50°C, let stand for 8 hours, take the supernatant AL-4 for use, analyze its composition, see Table 2.
[0070] The prepared supernatant AL-4 (polyaluminium chloride solution) and aluminium particles are added into a three-necked flask, wherein the mass ratio of the polyaluminium chloride solution to the aluminium particles is 3:9. A condensation reflux device is arranged on the top of the three-necked flask to reflux the water vapor carried away by the hydrogen in the reaction. The reaction liquid is heated to 85°C by electricity, and then reacted for 12 hours to obtain aluminium sol 4.
[0071] Example 3
[0072] According to the formulation in Table 1 below, add 1 kg of materials into a reactor, add distilled water first, then add aluminum hydroxide powder, turn on stirring, add industrial hydrochloric acid, steam heat to control the temperature of the reactor at 138-140°C, reaction pressure 0.5 MPa, react for 3 hours, then cool to 50°C, let stand for 8 hours, take the supernatant AL-6 for use, analyze its composition, see Table 2.
[0073] The prepared supernatant AL-6 (polyaluminium chloride solution) and aluminium particles are added into a three-necked flask, wherein the mass ratio of the polyaluminium chloride solution to the aluminium particles is 3:9. A condensation reflux device is arranged on the top of the three-necked flask to reflux the water vapor carried away by the hydrogen in the reaction. The reaction liquid is heated to 80°C by electricity, and then reacted for 14 hours to obtain aluminium sol 6.
[0074] Example 4
[0075] According to the formulation in Table 1 below, add 1 kg of materials into a reactor, add distilled water first, then add aluminum hydroxide powder, turn on stirring, add industrial hydrochloric acid, steam heat to control the temperature of the reactor at 138-140°C, reaction pressure 0.5 MPa, react for 4 hours, then cool to 50°C, stand for 8 hours, take the supernatant AL-8 for use, analyze its composition, see Table 2.
[0076] The prepared supernatant AL-8 (polyaluminium chloride solution) and aluminium particles were added into a three-necked flask, wherein the mass ratio of the polyaluminium chloride solution to the aluminium particles was 3:9. A condensation reflux device was arranged on the top of the three-necked flask to reflux the water vapor carried away by the hydrogen in the reaction. The reaction liquid was heated to 75°C by electricity, and then reacted for 16 hours to obtain aluminium sol 8.
[0077] Example 5
[0078] The method of Example 1 is used, except that during the preparation of the polyaluminium chloride solution, the temperature of the reactor is controlled at 140-145°C by steam heating, and the reaction is carried out for 3 hours to obtain aluminium sol 5.
[0079] Example 6
[0080] According to the method of Example 1, except that the mass ratio of the polyaluminium chloride solution to the aluminium particles is 2.5:9, thereby obtaining aluminium sol 7.
[0081] Comparative Example 1
[0082] The method of Example 1 is followed, except that during the preparation of the polyaluminium chloride solution, the reaction time is 2 hours to obtain aluminium sol 2.
[0083] Comparative Example 2
[0084] The method of Example 1 is used, except that, during the preparation of the polyaluminium chloride solution, the temperature of the reactor is controlled at 90-95°C by steam heating, and the reaction is carried out for 2 hours to obtain aluminium sol 3.
[0085] Table 1 Dissolution conditions of aluminum hydroxide powder
[0086] Aluminum hydroxide (calculated as Al) / % Industrial hydrochloric acid (as Cl) / % Example 1 7 20 Example 2 7 25 Example 3 9 25 Example 4 8 25 Example 5 7 25 Comparative Example 1 7 20 Comparative Example 2 3.5 10
[0087] Table 2 Analysis data of polyaluminium chloride solution
[0088] Al / % Cl / % Al dissolution rate / % Aluminum-chlorine ratio pH proportion Example 1 5.13 20 73.3 0.26 0.4 1.246 Example 2 6.5 25 92.8 0.26 0.3 1.298 Example 3 7.8 24.4 86.7 0.32 0.2 1.321 Example 4 8 25 100 0.32 0.3 1.366 Example 5 5.83 21 83.3 0.28 0.4 1.256 Comparative Example 1 4.83 18 69 0.27 0.5 1.223 Comparative Example 2 0.43 9 12.4 0.05 1.1 1.089
[0089] Table 3 Aluminum sol analysis data
[0090]
[0091]
[0092] Catalyst Preparation Example
[0093] According to the catalyst formulation in Table 4, aluminum sol was added to the reactor and stirred, and kaolin was added and stirred for 120 minutes; pseudo-boehmite was added and stirred for 30 minutes, and then hydrochloric acid (the mass ratio of hydrochloric acid to pseudo-boehmite was 0.2) was added and stirred for 60 minutes, and ground Y-type molecular sieve slurry (produced by Qilu Branch of Sinopec Catalyst Co., Ltd., with a slurry solid content of 31.4% by weight) was added, stirred for 30 minutes, spray-dried, and the obtained catalyst microspheres were calcined at 500°C for 1 hour; then the catalyst was washed twice with decationized water at a weight ratio of water: dry catalyst of 1:8, and dried at a constant temperature of 120°C for 2 hours to obtain catalyst products C1-C9 and D1-D4. The performance of the catalyst products is shown in Table 5.
[0094] Table 4
[0095]
[0096] Table 5
[0097] <![CDATA[Na2O]]> <![CDATA[Al2O3]]> <![CDATA[SiO2]]> <![CDATA[RE2O3]]> <![CDATA[SO3]]> Cl <![CDATA[Fe2O3]]> C1 0.15 54.4 37.2 3.87 1.69 0.25 0.26 C2 0.16 54.1 37.9 3.89 1.39 0.19 0.28 C3 0.15 55.3 36.6 3.82 1.42 0.21 0.26 C4 0.19 55.7 36.5 3.94 1.17 0.17 0.27 C5 0.14 53.5 38.3 3.78 1.17 0.25 0.29 C6 0.09 56.3 36.5 3.75 1.07 0.22 0.39 C7 0.0.9 55.6 37.4 3.73 0.98 0.16 0.36 D1 0.08 56.7 36.2 3.75 1.08 0.16 0.36 D2 0.09 56 37 3.67 1.05 0.2 0.37 C8 0.15 54.5 37.1 3.79 1.72 0.25 0.27 C9 0.13 54.1 36.8 3.88 1.65 0.23 0.30 D3 0.14 56.4 35 3.83 1.79 0.32 0.27 D4 0.19 55.3 37 3.95 1.1 0.19 0.3
[0098] Table 5 (continued)
[0099]
[0100] Among them, the bulk density, pore volume and attrition index of the catalyst were determined by RIPP31-90, RIPP28-90 and RIPP29-90 methods in "Petrochemical Analysis Methods, RIPP Test Method" (edited by Yang Cuiding, Science Press, published in 1990), respectively.
[0101] The evaluation of micro-antibody activity includes:
[0102] The catalyst was aged and deactivated at 800°C with 100% steam for 17 hours. The catalyst loading was 5 g, and the raw material was straight-run light diesel with a distillation range of 235-337°C. The raw material is shown in Table 6. The reaction temperature was 460°C, and the weight space velocity was 16 hours. -1 , the catalyst-oil ratio (weight) is 4, and the measured micro-reaction activity results are shown in Table 5. Wherein, micro-reaction activity = gasoline yield + gas yield + coke yield.
[0103] Table 6
[0104]
[0105] It can be seen from the data in Table 5 that the catalyst prepared by the aluminum sol prepared by the polyaluminum chloride of the present invention is basically equivalent to the catalyst prepared by the industrial aluminum sol A in terms of composition, specific surface area and other data; when the amount of aluminum sol in the catalyst formula is reduced, it can be seen from the catalyst data that the aluminum sol has better bonding properties and better catalyst performance.
[0106] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing aluminum sol, characterized in that: The method comprises reacting a polyaluminium chloride solution with aluminium to obtain an aluminium sol; wherein the preparation method of the polyaluminium chloride solution comprises the following steps: (1) Under the condition of introducing water vapor, aluminum hydroxide and hydrochloric acid are reacted at a temperature above 100° C. and a reaction time of more than 3 hours; (2) The product obtained by the reaction in step (1) is allowed to stand, and the supernatant is used as a polyaluminium chloride solution.
2. The method according to claim 1, wherein: In step (1), the reaction temperature is 100-140° C., the reaction time is 3-5 h, and the pressure is 0.1-0.6 MPa; Preferably, the mass fraction of the hydrochloric acid is 31-36%, and further preferably, the hydrochloric acid is industrial hydrochloric acid.
3. The method according to claim 1, wherein: In step (1), the amount of aluminum hydroxide and hydrochloric acid added is such that the mass percentage of aluminum in the obtained polyaluminum chloride solution is 5-9%, the mass percentage of chlorine is 20-27%, and the mass ratio of aluminum to chlorine is 0.2-0.45; Preferably, in step (1), the amount of aluminum hydroxide and hydrochloric acid added is such that the mass percentage of aluminum in the obtained polyaluminum chloride solution is 5-8%, the mass percentage of chlorine is 20-25%, and the mass ratio of aluminum to chlorine is 0.25-0.
35.
4. The method according to claim 1, wherein: The method further comprises cooling the product obtained by the reaction in step (1) before standing in step (2), preferably cooling it to below 60° C., more preferably cooling it to 30-50° C.
5. The method according to any one of claims 1 to 4, wherein: The standing time in step (2) is more than 3 hours, preferably 3-12 hours.
6. The method according to any one of claims 1 to 5, wherein: The pH value of the polyaluminium chloride solution obtained in step (2) is less than 1; And / or, the specific gravity of the polyaluminium chloride solution obtained in step (2) is 1.1-1.4 g / mL, preferably 1.24-1.4 g / mL.
7. The method according to any one of claims 1 to 6, wherein: Calculated on the basis of aluminum element, the mass ratio of polyaluminium chloride solution to aluminum is 2.5-3.5:8.5-9.5, preferably 2.5-3:8.5-9; Preferably, the conditions for reacting the polyaluminium chloride solution with aluminium include: a reaction temperature of 75-100° C. and a reaction time of 12-25 h.
8. Aluminum sol prepared by the method according to any one of claims 1 to 7; Preferably, the aluminum sol has an aluminum content of 11-12.5 weight %, a chlorine content of 7-11 weight %, a pH value greater than 2.6, and a specific gravity of 1.2-1.4 g / mL.
9. Use of the aluminum sol according to claim 8 as a binder in the preparation of a catalytic cracking catalyst.
10. A method for preparing a catalytic cracking catalyst, wherein: The method comprises: slurrying a binder, clay and a molecular sieve to obtain a catalyst slurry, and spray-drying the catalyst slurry. The method is characterized in that the binder contains the aluminum sol according to claim 8.
Citation Information
Patent Citations
A method for preparing aluminum glue and polyaluminum chloride
CN111320194B
High-Al13 aluminium trichloride polymer crystal and its prepn
CN1673089A